Stabilization protects islet integrity during respirometry in the Oroboros Oxygraph-2K analyzer. Issue 1 (31st December 2022) - Crowder, Justin J.; Zeng, Ziqian; Novak, Alissa N.; Alves, Nathan J.; Linnemann, Amelia K.
ABSTRACT: Metabolic dysfunction of β-cells has been implicated as a contributor to diabetes pathogenesis, and efforts are ongoing to optimize analytical techniques that evaluate islet metabolism. High-resolution respirometry offers sensitive measurements of the respiratory effects of metabolic substrates and customizable manipulation of electron transport chain components, though the delicate nature of islets can pose challenges to conventional analyses. An affordable and reliable option for respirometry is the Oroboros Oxygraph-2 K system, which utilizes a stir bar to circulate reagents around cells. While this technique may be suitable for individual cells or mitochondria, the continual force exerted by the stir bar can have damaging effects on islet integrity. Herein, we demonstrate the protective benefits of a novel 3D-printed islet stabilization device and highlight the destructive effects of conventional Oxygraph analysis on islet integrity. Islet containment did not inhibit cellular responses to metabolic modulatory drugs, as indicated by robust fluctuations in oxygen consumption rates. The average size of wild-type mouse islets was significantly reduced following a standard Mito Stress Test within Oxygraph chambers, with a clear disruption in islet morphology and viability. Alternatively, containment of the islets within the interior chamber of the islet stabilization device yielded preservation of both islet morphology and increased cell viability/survival after respirometry analysis. Collectively, our study introduces a new and easily accessible tool to improve conventional Oxygraph respirometry of pancreatic islets by preserving natural islet structure and function throughout metabolic analysis. Graphical abstract: uf0001